2003
DOI: 10.1161/01.cir.0000092912.57140.14
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Improvement After Combined Anterior Mitral Leaflet Extension and Myectomy in Hypertrophic Obstructive Cardiomyopathy

Abstract: Background-Mitral leaflet extension (MLE) combined with septal myectomy is a new surgical approach to treat hypertrophic obstructive cardiomyopathy (HOCM) and an enlarged mitral leaflet area. The study presents the long-term clinical results and outcome of this technique. Methods and Results-MLE entails grafting a glutaraldehyde-preserved autologous pericardial patch onto the center portion of the anterior mitral valve leaflet. Twenty-nine patients with HOCM were studied. Mean follow-up (ϮSD) was 3.4Ϯ2.1 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 32 publications
1
54
0
2
Order By: Relevance
“…[25][26][27][28][29][30] The observation that mitral valve length is associated with outflow obstruction in some patients has implications for management strategies in this disease. [31][32][33][34][35][36][37][38][39][40] Elongated mitral leaflets create 2 potential problems. First, the mitral-septal contact point (and site of subaortic obstruction) can be displaced distal to its usual position, creating the necessity for an extended muscular resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30] The observation that mitral valve length is associated with outflow obstruction in some patients has implications for management strategies in this disease. [31][32][33][34][35][36][37][38][39][40] Elongated mitral leaflets create 2 potential problems. First, the mitral-septal contact point (and site of subaortic obstruction) can be displaced distal to its usual position, creating the necessity for an extended muscular resection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of surgical reports of severely symptomatic obstructive HCM patients promote the combined approach of septal myectomy and AML repair, with leaflet extension or shortening reconstruction or plication. 31,32,37,39,41 In this regard, van der Lee et al 37 reported that 90% of their operated patients over an 8-year period were judged by the surgeon to have particularly elongated mitral leaflets that would have made myectomy alone unlikely to yield optimal hemodynamic results.…”
Section: Discussionmentioning
confidence: 99%
“…As there is a direct relation between volume of myectomies performed and surgical outcomes, optimal results cannot be expected from surgeons with a low-volume exposure to symptomatic patients with obstructive HCM (1,15,16). Therefore, the best results have been obtained by those few surgeons in the world with extensive myectomy experience and a small number of referral centers in North America and Europe (5,7,11,(17)(18)(19)(20). This represents an important obstacle to bringing septal myectomy to the HCM population.…”
Section: Surgical Septal Myectomymentioning
confidence: 99%
“…A number of novel valve repair techniques have been developed that reduce the contribution of the mitral valve apparatus to outflow obstruction. Such techniques include mobilization of the papillary muscles, secondary anterior leaflet chordal cutting, and extension or plication of the anterior mitral leaflet (11,18,19). Of note, septal myocardial infarction caused by alcohol cannot abolish the outflow gradient in HCM patients where abnormalities of the mitral valve apparatus play a major role in LV outflow obstruction and in many instances, mitral valve abnormalities would exclude alcohol ablation as a viable treatment option.…”
Section: Morphologic Complexity Of Hcmmentioning
confidence: 99%
“…In HOCM, abnormal anatomy and valve displacement induce drag forces that cause SAM. This condition can be corrected by an autologous pericardial patch in the anterior mitral leaflet (32) .…”
Section: Discussionmentioning
confidence: 99%